Numerical modelling of tunnel fires and water mist suppression - Hart, Robert (2006)
Fires in mine tunnels and other underground space are a serious hazard, that can, if left unchecked, result in significant economic loss and human tragedy. In the UK, methods such as water deluge, foam application, and various types of handheld extinguishers have been used, but statistics show no improvement in the incidence of fire. Water mist has the potential to be an effective fire suppression system for tunnel spaces. Typical water mist systems utilise small droplets of around 100 micron that have a low terminal velocity and a high surface to volume ratio. This leads to behaviour distinct from that of traditional sprinklers. Various mechanisms of action have been identified: removal of heat; oxygen depletion; fuel cooling; attenuation of radiation; and disruption of air flow. The relative importance of each is case dependent.